Перспективи використання видів та культиварів роду форзиція (Forsythia Vahl.) у зеленому будівництві в Правобережному Лісостепу України - Goncharenko, B.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
The perspectives of wider usage of Forsythia genus species and cultivars in landscape design in Right-Bank Forest-Steppe of Ukraine was studied on the base of analysis of their growing. The most perspective Forsythia species and cultivars introduction have been found.